THE DIFFERENCE EFFECT BETWEEN AUTO STRETCHING AND MYOFASCIAL RELEASE ON IMPROVING HIP RANGE OF MOTION IN PIRIFORMIS SYNDROME - Hilda Dea Revani; Dina Istiana; Firnanda Erindia (SYNTIFIC, 2026)
Background. Piriformis syndrome is a neuromuscular disorder linked to tightness or spasms of the gluteal muscles, leading to hip pain and restricted range of motion (ROM). Physiotherapy methods like auto stretching and myofascial release (MFR) are frequently used to enhance hip ROM. This study aimed to determine difference effect between autostretching and myofascial release on improving hip ROM in piriformis syndrome. Research Method. This study employed a quasi-experimental design involving 30 participants selected using a matching allocation technique. Subjects were divided into two groups, each consisting of 15 participants: Group I received auto stretching, and Group II received myofascial release. The interventions were conducted for four weeks, three times per week. Hip ROM was measured using a goniometer before and after the intervention. Data were analyzed using paired t-tests and independent t-tests with a significance level of p<0.05. Findings. The Shapiro–Wilk test indicated the data were both normally and non-normally distributed, while Levene’s test showed homogeneity of variance. Hypothesis testing using paired sample t-tests demonstrated significant improvements in hip ROM in Group I (p = 0.000; p < 0.05) and Group II (p = 0.000; p < 0.05). Independent t-test analysis revealed a significant difference between the two intervention groups (p = 0.007; p < 0.05), indicating a statistically significant difference in outcomes. Conclusion. Both myofascial release and self-stretching are effective in improving hip range of motion in cases of piriformis syndrome, but myofascial release results in a more significant improvement in range of motion in the short term.